The effectiveness of frog VLE implementation: students’ perspective - Rogayah Abdul Majid; Juhaida Che Hasim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the effectiveness of the Frog VLE implementation from students’ perspectives. Virtual Learning Environment (VLEs) is an online systems supporting interactions between and amongst learners and teachers in school. The Frog VLE is a web-based learning system that replicates real life learning by incorporating virtual learning equivalent of traditional concepts of education with the aim to  enhance the learning experience beyond the bounded classroom background. Previous studies have identified some difficulties in the Frog VLE implementation such as competency of the teachers and student, facilities and infrastructure of implementing the Frog VLE in school. Therefore, the aim of this study is to measure the effectiveness of the Frog VLE implementation from student perspective as VLE platform may lead to the performance improvement among the students. A survey was conducted with 315 participants,  consists of Year 4 and Year 5 primary school students in Shah Alam. The result of the study shows that from the “nature of student self, teacher’s competency, useful and ease of use of the application, and conducive learning environment have improve students’ academic performance and motivation.